Does political representation through parties decrease voters' acceptance of decisions - Emanuel Vahid Towfigh; Andreas Glöckner; Sebastian J. Goerg; Philip Leifeld; Carlos Kurschilgen; Aniol Llorente-Saguer; Sophie Bade (Max Planck Institute for Research on Collective Goods, 2013)
Are decisions by political parties more or less accepted than direct-democratic decisions? The literature on parties as brand names or labels suggests that the existence of political parties lowers information and transaction costs of voters by providing ideological packages. Building on this important argument, we posit that this informational rationale for parties is not universally applicable and is contingent on the context of the decision that is made. Intermediary political decision-making institutions may impose additional costs on voters in situations where the decision is perceived to be personally important to the individual voter. We conduct an experimental online vignette study to substantiate these claims. The results imply that a combination of representative democracy and direct democracy, conditional on the distribution of issue importance among the electorate, is optimal with regard to acceptance of a decision.
Keywords: 330